Effects of Fusarium graminearum and Fusarium poae on disease parameters, grain quality and mycotoxin contamination in barley (part II) - Martínez, Mauro (2020)
BACKGROUND: Barley is one of the most important winter crops in the world, with multiple uses such as human consumption, animal feed and for the malting industry. This crop is affected by different diseases, such as Fusarium Head Blight (FHB), that causes losses in yield and quality. In the last years F. graminearum and F. poae were two of the most frequently isolated species in barley grains, so the aim of this study was to evaluate the interaction between these Fusarium species and the effects on disease parameters, grain quality and mycotoxin contamination on five barley genotypes under field conditions. RESULTS: Statistical differences between Fusarium treatments for some parameters depending mainly on the year/genotype were found. The results showed that germination process was affected by both Fusarium species. As to grain quality and the different hordein fractions, it was observed that F. graminearum affects preferentially D and C hordeins Different concentrations of nivalenol, deoxynivalenol and their acetylated derivatives (3-ADON and 15-ADON) were detected. CONCLUSIONS: In the present work, no evidence of synergism between F. graminearum and F. poae were found regarding disease parameters and mycotoxin contamination. However, at least in the years with favorable climatic conditions to FHB development and depending on the barley genotype, a continuous monitoring is deemed necessary to prevent the negative impact on protein composition and germinative parameters